The interplay of critical language pedagogy and young Arabic EFL learners - Nelson, Nadine; Chen, Julian (Taylor & Francis, 2023)
This paper is based on the first author’s experience of experimenting with critical language pedagogy (CLP) when she was teaching in the UAE. While prior research focuses mainly on the theoretical aspects of CLP, empirical studies on the effectiveness of implementing critical approaches and developing related teaching materials in Arab EFL contexts with young learners are underrepresented. Informed by Paulo Freire’s formulation of ‘culture circles’, this case study reports on the problem-posing literacy practice in a class of Grade 4 female Arabic students in an Abu Dhabi government school—a sample unique to both CLP and case study research. Results indicate EFL learners’ increased capacity for problem posing and motivation for writing, metacognition, and application of prior knowledge during the pre-writing discussion. Findings of this study add evidence-based, practical dimensions to existing critical research, paving the way for like-minded language educators to trial CLP with young learners.